Deficiências de macronutrientes, Fe e B em manjericão (Ocimum sp.), em cultivo hidropônico - AMARAL, JOSE FRANCISCO TEIXEIRA DO; FONSECA, AYMBIRÉ FRANCISCO ALMEIDA DA; MARTINEZ, HERMINIA EMILIA PIETRO; PEREIRA, PAULO ROBERTO; FONTES, PAULO CEZAR RESENDE (Revista Ceres, 2015)
.